Impact of Peripheral Field Loss on the Execution of Natural Actions: A Study With Glaucomatous Patients and Normally Sighted People. Issue 10 (October 2016) - Dive, Stéphanie; Rouland, Jean F.; Lenoble, Quentin; Szaffarczyk, Sebastien; McKendrick, Allison M.; Boucart, Muriel
Abstract : Purpose: We investigated the visuomotor behavior of people with reduced peripheral field due to glaucoma while they accomplished natural actions. Methods: Twelve participants with glaucoma and 13 normally sighted controls were included. Participants were asked to accomplish a familiar sandwich-making task and a less familiar model-building task with a children's construction set while their eye movements were recorded. Both scene layouts contained task-relevant and task-irrelevant objects. There was no time constraint. Results: Participants with glaucoma were slower to perform the task than were the normal observers, but the slower performance was confined to the unfamiliar model-building task. Patients and controls were equally efficient in the more familiar sandwich-making task. On initial exposure, before the first reaching movement was initiated, patients scanned the objects longer than did controls, particularly in the unfamiliar model-building task, and controls fixated irrelevant objects less than did patients. During the working phase fixations were on average longer for patients than for controls and patients made more saccades than did controls. Patients did not grasp more irrelevant objects compared with controls. Conclusions: The results provide evidence that, although slower than controls, patients with glaucoma were able to accomplish natural actions efficiently even when the task required discrimination of small structurally similar objects (nuts and screws in the model-building task). Their difficulties were reflected in longer fixation times and more head and eye movements compared with controls, presumably to compensate for lower visibility when objects fell in the part of their visual field where sensitivity was reduced.